Relationship between Job Satisfaction and Length of Service with Caring Behavior of Nurses at RSUD Dr. Abdul Rivai Berau District - Krismas Setiyani; Lamri; Arsyawina (Formosa Journal of Multidisciplinary Research, 2023)
Hospital services focus on treatment so that it demands caring behavior in the implementation of quality nursing care. The impact of nursing services due to job satisfaction is manifested in the form of service quality. This study aims to determine the relationship between job satisfaction and length of service with caring behavior of nurses. This type of research is analytic observational with a Speaman rank with a significance level of 0.05. cross sectional design with a total sample of 67 nurses taken purposively. The average nurse's tenure was 12.79 years, the average nurse's job satisfaction was 55.477, and the average nurse's caring behavior was 77.940. There is a fairly strong relationship between job satisfaction and caring behavior of nurses (Sig = 0.000; Correlation = 0.448), and there is a low relationship between length of service and caring behavior of nurses (Sig = 0.004; Correlation = -0.344).